Multitarget mechanism of MYC inhibition by the bacterial lon protease in disease - Ines Ambite; Murphy Lam Yim Wan; Hien Thi Tran; Atefeh Nazari; Arunima Chaudhuri; Christian Krintel; Inês Gomes; Samudra Sabari; Shahram Ahmadi; António N. B. M. Carneiro; Rita Ishac; Farhan Haq; et al. (Scientific Reports)
Abstract Identifying specific inhibitors of the MYC oncogene has been challenging, due to off target effects associated with MYC inhibition. This study investigated how the recombinant Escherichia coli Lon protease (rLon), which targets MYC in human cells, inhibits MYC over-activation in models of infection and cancer. In silico predictions identified specific peptide domains of bacterial Lon that target MYC and the affinity of these peptides for MYC was investigated by surface plasmon resonance. The N-terminal domain of rLon was shown to interact with the C-terminal, leucine zipper domain of MYC and MAX and to prevent MYC/MAX dimerization. Furthermore, rLon targeted and degraded c-MYC in vitro and in cellular models, through the peptidase domain. In a model of kidney infection, rLon treatment prevented, c-MYC, N-MYC and L-MYC over-expression, MYC-dependent gene expression, specifically renal toxicity genes and pathology, suggesting that rLon recognizes and corrects MYC dysregulation in this disease. The findings describe a multitarget mechanism of MYC inhibition by rLon, and the combined effects achieved by the Lon domains, targeting different MYC epitopes and MYC-dependent functions, with no evidence of toxicity or detrimental effects on homeostatic MYC expression.